Exceptional TcO4− sorption capacity and highly efficient ReO4− luminescence sensing by Zr4+ MOFs. Issue 42 (16th October 2018) - Rapti, Sofia; Diamantis, Stavros A.; Dafnomili, Argyro; Pournara, Anastasia; Skliri, Euaggelia; Armatas, Gerasimos S.; Tsipis, Athanassios C.; Spanopoulos, Ioannis; Malliakas, Christos D.; Kanatzidis, Mercouri G.; Plakatouras, John C.; Noli, Fotini; et al.
Abstract : A Zr 4+ MOF shows an exceptional capability to capture TcO4 − and selective luminescence sensing for ReO4 −, demonstrated for the first time for MOF materials. Abstract : The sorption properties of [Zr6 O4 (OH)4 (NH3 + -BDC)6 ]Cl6 · x H2 O (MOR-1 ) and H16 [Zr6 O16 (H2 PATP)4 ]Cl8 · x H2 O (MOR-2 ) towards ReO4 − and TcO4 − were studied in detail. BothMOR-1 andMOR-2 are very effective sorbents for ReO4 − and TcO4 − anions, withMOR-2 showing the highest sorption capacity (up to 4.1 ± 0.4 mmol g −1 ) among the known metal organic materials. Importantly, the exceptional sorption capacity ofMOR-2 is retained even under conditions simulating acidic nuclear waste. In addition, MOR-1 andMOR-2 exhibit selective luminescence ReO4 − sensing properties, demonstrated for the first time for MOF materials.